Mockingbird Morphing Music: Structured Transitions in a Complex Bird Song - Roeske, Tina C.; Rothenberg, David; Gammon, David E. (Frontiers in Psychology, 2021)
The song of the northern mockingbird, Mimus polyglottos, is notable for its extensive length and inclusion of numerous imitations of several common North American bird species. Because of its complexity, it is not widely studied by birdsong scientists. When they do study it, the specific imitations are often noted, and the total number of varying phrases. What is rarely noted is the systematic way the bird changes from one syllable to the next, often with a subtle transition where one sound is gradually transformed into a related sound, revealing an audible and specific compositional strategy. It resembles a common strategy in human composing, which can be described as variation of a theme. In this paper we present our initial attempts to describe the specific compositional rules behind the mockingbird song, focusing on the way the bird transitions from one syllable type to the next. We find that more often than chance, syllables before and after the transition are spectrally related, i.e. transitions are gradual, which we define as a musical ‘morphing.’ In our paper we categorize four common kinds of morphing: timbre change, pitch change, squeeze, and stretch. This is the first time such transition rules in any complex birdsong have been specifically articulated.